The Effect of NPK Fertilizer and Vermicompost Application on Plant Growth and The Nutrient Contents of Radish (Raphanus Sativus L.) - Ayşen Akay (Turkish Journal of Agriculture: Food Science and Technology)
Vermicompost production and applications are increasing in our country recently. There are also many commercial products on the market. Vermicompost may act both as soil conditions and organic fertilizer. In addition to the effect of this product on improving the physical properties of the soil; the effect of plant growth on different plants should be studied. In this study conducted for this purpose; commercially produced radish (Raphanus sativus L.) cv. “Cherry Belle” was planted in growing medium mixed with different doses of vermicompost (0 - 2.5 – 5 – 10 %). In order to determine NPK and NPK + Fe. Zn fertilizer needs of the plants, these elements contained fertilizers were applied. According to the pot experiment results, important increases in some element contents and fresh root weights of radish plant were determined with increasing vermicompost applications. The average fresh root weight changed between 47.89-77.70 g pot-1. The average N concentration of in leaves and in roots changed between 3.09-4.69 % and 1.19-2.67 %, respectively. The K of in leaves and in roots changed between 1.27-1.46 % and 1.39-2.13 %, respectively, and the P concentration of in leaves and in roots changed between 0.46-0.50 % and 0.36-0.45 %, respectively. Application of vermicompost had statistically significant effect on growth of radish.